An Input-Output Analysis of the Information and Communication Technologies Sector in Turkey - Tunç, Tulin; Nas, Şahin; Demir, Eylül Ece (SOSYOEKONOMI SOC, 2022)
omies have become an important subject. After observing that ICTs production and consumption affect countries, these effects are analysed with various empirical methods. This study aims to determine the impact of the ICTs sector on the other sectors of Turkey using the input-output analysis. The analysis is made for 2000 and 2014 based on data from the World Input-Output Database. In studies of the literature, it has been determined that this sector has an essential contribution to the growth and development of the economy. In this study, it was concluded that the contribution of the ICTs sector to the added value and employment in the economy remains low due to the small share of the Turkish economy in production

Bilgi ve iletişim teknolojilerinin (BİT) kullanımının yaygınlaşmasıyla birlikte dünyanın bilgi çağına girdiği kabul edilmektedir. BİT üretiminin ve tüketiminin ülke ekonomilerini etkilediğinin gözlemlenmesi üzerine, bu etkiler çeşitli ampirik yöntemler ile analiz edilmeye başlanmıştır. Bu çalışmada da Dünya Girdi-Çıktı Veri Tabanından elde edilen veriler kapsamında, 2000 ve 2014 yılları için Türkiye’de, BİT sektörünün diğer sektörler üzerindeki etkisini ve dolayısıyla Türkiye ekonomisindeki yerini belirlemek üzere bir girdi-çıktı analizi uygulanmıştır. Literatürde yer alan çalışmalarda, ekonomilerde büyüme ve kalkınmaya önemli bir katkısı olduğu belirlenen BİT sektörünün, Türkiye ekonomisinde üretimdeki payının küçük olması nedeniyle katma değere ve istihdama katkısının düşük kaldığı tespit edilmiştir.
Keywords: Input-Output Analysis; ICTs Sector; Turkey; Girdi-Çıktı Analizi; BİT Sektörü; Türkiye